2018
DOI: 10.1136/bmjopen-2017-019557
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia, hyperglycaemia and worsening renal function at first blood sample on emergency department admission as predictors of in-hospital death in patients with dyspnoea with suspected acute heart failure: retrospective observational analysis of the PARADISE cohort

Abstract: ObjectivesTo assess the prognostic value of hyponatraemia, hyperglycaemia and impaired estimated glomerular filtration rate (eGFR) in predicting in-hospital death in patients with acute heart failure (AHF) admitted for acute dyspnoea in the emergency department.DesignRetrospective observational study.SettingEmergency Department of the University Hospital of Nancy. Data were collected from August 2013 to October 2015.ParticipantsThe analysis included 405 patients with AHF admitted for acute dyspnoea in an emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…In the present study, irrespective of DM, admission HGL was a significant predictor of IHD in AHF, but DM was not a predictor of IHD. Several studies also have shown that HGL is an independent predictor of IHD in patients with AHF [13][14][15][16]. Sud et al also showed that mildly elevated presentation blood glucose is associated with 30-day mortality and hospitalization in AHF patients with no pre-existing DM [16].…”
Section: Admission Hgl or Dm And Ihdmentioning
confidence: 99%
“…In the present study, irrespective of DM, admission HGL was a significant predictor of IHD in AHF, but DM was not a predictor of IHD. Several studies also have shown that HGL is an independent predictor of IHD in patients with AHF [13][14][15][16]. Sud et al also showed that mildly elevated presentation blood glucose is associated with 30-day mortality and hospitalization in AHF patients with no pre-existing DM [16].…”
Section: Admission Hgl or Dm And Ihdmentioning
confidence: 99%
“…Indeed, the Brest score efficiently rules out AHF diagnosis for scores < 4 and affirms the diagnosis for scores > 9. However, for patients with an intermediate score (4)(5)(6)(7)(8), other complementary tools (biomarkers and/or LUS) 9 seemingly appear necessary to improve diagnostic accuracy 19 .…”
Section: Brest Score and Ahfmentioning
confidence: 99%
“…Prognosis is related to initiation time of specific therapies 5 . In-hospital mortality is typically reported to be greater than 10% 6 and has remained stable in the last 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…This study is reported as per the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) guideline ( S1 Checklist ). The Pathway of dyspneic patients in Emergency (PARADISE) cohort is a retrospective cohort study including consecutive patients aged 18 years or older who were admitted for acute dyspnea in the ED of the Nancy University Hospital (France) between January 1, 2015 and December 31, 2015 as detailed previously [ 21 , 22 ]. The hospital’s electronic charts (resurgences) were systematically reviewed by investigators to search for the records of all patients admitted for acute dyspnea in the ED.…”
Section: Methodsmentioning
confidence: 99%